What comes next? (Economist, 2023)
The article discusses about the abilities of large language models (LLMs). It states that text-generating prowess of LLMs allow them to act as general-purpose reasoning engines. Topics discussed include prospect of connecting LLMS to real-world contraptions, LLMs with formal reasoning capabilities and power generative-Al models.